2016
DOI: 10.1016/j.ajog.2016.02.045
|View full text |Cite
|
Sign up to set email alerts
|

Serum vitamin D status and bacterial vaginosis prevalence and incidence in Zimbabwean women

Abstract: BACKGROUND Bacterial vaginosis, a highly prevalent vaginal condition, is correlated with many adverse reproductive outcomes. In some studies, low vitamin D (measured as serum 25-hydroxy-vitamin D, 25(OH)D) has been associated with increased prevalence of bacterial vaginosis. OBJECTIVES We examined the cross-sectional association between vitamin D status and prevalence of bacterial vaginosis, separately for pregnant and non-pregnant women. Using prospectively-collected data, we also characterized the effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 44 publications
1
17
1
Order By: Relevance
“…Based on our literature review (See Additional file 1: Table S1), most previous studies examining relationships between micronutrients and BV focused on serum vitamin D. However, study designs were heterogeneous, and results were conflicting. Five studies (1 longitudinal and 4 cross-sectional observational studies) showed an increased risk of BV with low vitamin D [9, 1618, 20], but three studies (all cross-sectional observational studies) [8, 11, 14] suggested no association, or even a reverse association with low vitamin D. Two randomized controlled trials examined vitamin D supplementation. One showed some benefit in asymptomatic BV [12], while another showed no improvement with symptomatic BV recurrence in vitamin D supplementation [13].…”
Section: Discussionmentioning
confidence: 99%
“…Based on our literature review (See Additional file 1: Table S1), most previous studies examining relationships between micronutrients and BV focused on serum vitamin D. However, study designs were heterogeneous, and results were conflicting. Five studies (1 longitudinal and 4 cross-sectional observational studies) showed an increased risk of BV with low vitamin D [9, 1618, 20], but three studies (all cross-sectional observational studies) [8, 11, 14] suggested no association, or even a reverse association with low vitamin D. Two randomized controlled trials examined vitamin D supplementation. One showed some benefit in asymptomatic BV [12], while another showed no improvement with symptomatic BV recurrence in vitamin D supplementation [13].…”
Section: Discussionmentioning
confidence: 99%
“…Despite our findings of an association between serum 25(OH)D and BV, the present study did not find an association between frank vitamin D deficiency (defined as serum total 25(OH)D < 20 ng/mL) and the occurrence of BV. A cohort of Zimbabwean pregnant women also failed to find an association with vitamin D deficiency and BV [35]. In contrast, a cross-sectional study of 440 US pregnant, selected to be representative of the racial-ethnic composition of women of reproductive age in the US, did find that total 25(OH)D < 30 ng/mL (a category combining vitamin D insufficiency and vitamin D deficiency) significantly increased the odds of BV [36].…”
Section: Discussionmentioning
confidence: 99%
“…The study of Zimbabwean pregnant women was the first to examine the association between time-varying vitamin D and BV using cohort data, finding that among women who did not have BV at enrollment, deficient or insufficient vitamin D was not associated with incident BV during follow-up [35]. The present study did find an association with change in 25(OH)D from early to later pregnancy, as a continuous measure but not as a categorical measure, and BV later in pregnancy adjusting for baseline Nugent score and 25(OH)D. Further research is needed to confirm this association in other cohorts with measurement of measures of 25(OH)D at more than a single time point in pregnancy and to understand clinical and behavioural factors that may drive changes in vitamin D concentrations during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…23 Studies on the association between vitamin D and BV have had mixed findings. Among pregnant women, one observational study found a null association, 24 but most have found a higher prevalence of BV among those who are vitamin D deficient or insufficient. [25][26][27][28] In addition, a randomized controlled trial (RCT) found a trend of lower rates of BV with increasing doses of vitamin D, although they were nonsignificant.…”
Section: Introductionmentioning
confidence: 99%